Pelaksanaan Kecerdasan Kinestetik Anak Usia Dini di Taman Kanak Negeri II Padang Pasir: Implementation of Early Childhood Kinesthetic Intelligence in Padang Pasir II State Kindergarten - Yamifebrianti Yamifebrianti; Indra Yeni (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The purpose of this study is to describe the implementation of early childhood kinesthetic intelligence in State Kindergarten (TK) II Padang Pasir which uses a variety of strategies different from other kindergartens. This type of research is descriptive qualitative research with the aim of describing the implementation of early childhood kinesthetic intelligence in State Kindergarten II Padang Pasir. The data collection technique is by using observation, interview, and documentation techniques. The results of this study in general that the implementation of early childhood kinesthetic intelligence in State Kindergarten II Padang Pasir is carried out as expected by referring to the standard indicators of children's development achievement levels. The implementation of kinesthetic intelligence in early childhood begins with designing learning, making and providing learning media. The teacher in using the strategy is in accordance with what has been planned. Strategies carried out by demonstration, direct practice, child-centered, guided inquiry, integrated learning and according to the needs of children. Evaluation in kinesthetic intelligence to see what indicators have developed in children using anecdotal record techniques, rating scales, and children's work. The results of research conducted at State Kindergarten II Padang Pasir on the implementation of children's kinesthetic intelligence in State Kindergarten II Padang Pasir can be concluded that the implementation of children's kinesthetic intelligence is in accordance with the beginning of learning which includes determining subjects, sub-topics, learning materials and program planning, creating and providing learning materials related to subjects and sub-sub topics. Teachers as strategic developers use methods and materials and research that are in accordance with the application of positive kinesthetic intelligence that has been determined.